Additions to the Odonata (Insecta) of Goa - P. Rangnekar; M. Borkar; O. Dharwadkar (Journal of Threatened Taxa, 2010)
The study reports the results from surveys for Odonates in the State of Goa over 19 months during 2007-2008. A total of 66 species of Odonates were documented with 34 new species records from the State. The present study has resulted in an increase of 47.30% in the number of species reported from Goa to 74 from the existing 39. Family Libellulidae dominated the odonate community with 32 species followed by Coenagrionidae with 14 species. Orthetrum sabina was the most abundant species while seven species were documented only once during the survey period. More survey effort are needed to completely document the odonate species diversity of the state.